Aspergillus niger Fermentation Broth Promotes Maize Germination and Alleviates Low Phosphorus Stress - Maoxian Tian; Changhui Zhang; Zhi Zhang; Tao Jiang; Xiaolan Hu; Hongbo Qiu; Zhu Li (Microorganisms, 2023)
Aspergillus niger is a type of soil fungus with the ability to dissolve insoluble phosphate and secrete organic metabolites such as citric acid. However, whether cell-free Aspergillus niger fermentation broth (AFB) promotes maize growth and alleviates low-phosphorus stress has not been reported. In this study, we explored their relationship through a hydroponics system. The results indicated that either too low or too high concentrations of AFB may inhibit seed germination potential and germination rate. Under low phosphorus conditions, all physiological indexes (biomass, soluble sugar content, root length, etc.) increased after AFB was applied. A qRT-PCR analysis revealed that the expression of the EXPB4 and KRP1 genes, which are involved in root development, was upregulated, while the expression of the CAT2 and SOD9 genes, which are keys to the synthesis of antioxidant enzymes, was downregulated. The expression of LOX3, a key gene in lipid peroxidation, was down-regulated, consistent with changes in the corresponding enzyme activity. These results indicate that the application of AFB may alleviate the oxidative stress in maize seedlings, reduce the oxidative damage caused by low P stress, and enhance the resistance to low P stress in maize seedlings. In addition, it reveals the potential of A. niger to promote growth and provides new avenues for research on beneficial plant-fungal interactions.